2015
DOI: 10.1017/s0029665115000166
|View full text |Cite
|
Sign up to set email alerts
|

Examination of methylglyoxal levels in an in vitro model of steatosis and serum from patients with non-alcoholic fatty liver disease

Abstract: This abstract was presented as the Cellular and Molecular Nutrition Theme highlight.Elevated levels of methylglyoxal (MG), a highly reactive glycating agent forming advanced glycation endproducts (AGEs), have been associated with diabetes, obesity and vascular disease (1) . However, its role in the hepatic manifestation of metabolic syndrome, nonalcoholic fatty liver disease (NAFLD), is still a novel inquiry. The objective of these experiments was to assess MG levels in response to lipid loading in the liver.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…15 However, some studies have shown the involvement of MGO in liver diseases. [16][17][18] We were curious to know whether MGO creates an ambience for cancer in the liver cells. So, we put forth a hypothesis that MGO could trigger metabolic reprogramming to induce cancer development in the HepG2 cells through its multifaceted pathologies like the Warburg effect and glycation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 However, some studies have shown the involvement of MGO in liver diseases. [16][17][18] We were curious to know whether MGO creates an ambience for cancer in the liver cells. So, we put forth a hypothesis that MGO could trigger metabolic reprogramming to induce cancer development in the HepG2 cells through its multifaceted pathologies like the Warburg effect and glycation.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown the involvement of MGO in liver diseases 16–18 . We were curious to know whether MGO creates an ambience for cancer in the liver cells.…”
Section: Introductionmentioning
confidence: 99%
“…Despite various reports on MGO-AGE-mediated toxicity in different organs, its role in the liver system is yet to be reported. By using LC-MS/ MS, it was found that increased MG and MGO-AGEs formation in hepatic steatosis in vivo may be localized to the liver (Maldonado et al, 2015). Previous studies focused on the pathophysiology of NAFLD with special emphasis on the role of AGEs in NAFLD progression to non-alcoholic steatohepatitis and liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%